The Influence of Capital Market Knowledge, Fundamental Analysis, Technical Analysis, and Locus of Control on Stock Investment Decisions Among Gen Z - Rena Novita; Wiliam Santoso; Cliff Kohardinata (Green Publisher Indonesia, 2025)
Generation Z has emerged as a significant force in capital markets, with their investment participation growing substantially in recent years. However, understanding the factors influencing their investment decisions remains limited, particularly in emerging markets such as Indonesia. This research aims to analyze the influence of capital market knowledge, fundamental analysis, technical analysis, and locus of control on stock investment decisions among Generation Z investors in Jambi Province, Indonesia. The study employed a quantitative approach using purposive sampling with 220 respondents aged 18–30 years who are active stock investors. Data were collected through online questionnaires and analyzed using multiple linear regression with SPSS 22. The results indicate that all three independent variables—fundamental analysis (β = 0.163, p < 0.05), technical analysis (β = 0.361, p < 0.05), and locus of control (β = 0.205, p < 0.05)—have significant and positive influences on investment decisions. Technical analysis demonstrates the strongest effect, followed by locus of control and fundamental analysis. These findings reveal that Generation Z's investment decisions are shaped by both analytical capabilities (fundamental and technical analysis) and psychological factors (locus of control). The research contributes to financial literacy development by providing insights for the Indonesia Stock Exchange and securities companies to design more effective educational programs tailored to Generation Z’s characteristics, ultimately promoting more informed and rational investment decision-making among young investors.